Peculiarities of implementation of mobile learning of foreign languages at the economic university - O. O. Karpova (Academy of Cognitive and Natural Sciences, 2017)
The aim of the study is to improve the process of teaching a foreign language using multimedia tools in general, and mobile learning in particular. The objectives of the study are the analysis of modern forms, methods and tools of teaching a foreign language with ICT tools, their selection and experimental study of their effectiveness. The object of the research is the process of teaching a foreign language to students of economic specialties. The subject of the research is the use of ICT tools in students' study and research work. The following methods of research have been used: testing, questionnaires, experimental research, interviews and consultations. The analysis, generalization and systematization of researches on the problem of teaching a foreign language at higher educational establishments with the use of multimedia tools have been made as well as the experimental implementation of multimedia technologies along with mobile learning to teaching a professionally-oriented foreign language has been conducted. The results of the study are planned to be published to implement mobile learning in teaching a foreign language to future economists.